Right-Wing Populism and Vigilantism: Comparing Cases of Indonesia and India - Zahra Nasywa Imtiyaz; Adhi Cahya Fahadayna (JED (Jurnal Etika Demokrasi), 2023)
This study explores the rise and impact of right spectrum populism in Indonesia and India, focusing in which religious-majority vigilante groups advocate for different interests within the socio-political context. Drawing on comparative method analysis, this research aims to examines the similarities and differences between these two countries, which are considered as significant representations of democracies in Asia. By employing Mill's methods of difference, the study investigates the factors contributing to the emergence and growth of right-wing populism, analyzing political and socio-cultural contexts. Through utilizing this research approach, the study aims to provide a comprehensive understanding of the complex dynamics surrounding right-wing populism in Indonesia and India, shedding light on the challenges faced by democratic societies in the face of rising populist movements. The research highlights the role of religious identity, electoral dynamics, and the mobilization of mass support in shaping the ideologies and actions of right-wing populist movements. Furthermore, this research found that populist movements have achieved some degree of political dominance through changes in electoral and legislative realms, they also employed vigilantism as a method to establish the supremacy of the majority religion they claim to represent. At the final section, this study prove the main difference in bothe country emerges in the resistance and magnitude of societal polarization and violence.